Impact Des Caractéristiques De La Végétation Sur La Diversité D’usages Des Plantes Autour De Deux Grandes Forêts Classées Et D’une Réserve Botanique Au Sud-Bénin - Joel, Avikpo Dansou; Hospice, Dassou Gbèwonmèdéa; Cossi, Adomou Aristide; Aristide, Houenon Gbèdomèdji Hurgues; Brice, Tente; Brice, Sinsin Augustin (European Scientific Journal, ESJ, 2017)
Southern-Benin has a mosaic of ecological conditions that have contributed to the development of its vast forest heritage. The combination of a number of parameters or indices (use value, diversity index, and equitability and citation frequency) is an effective way of identifying the most important plants for preservation. The objective was to carry out the checklist of the plants used around the classified forests of Ahozon and Lama and the botanical reserve of Pobè in Southern-Benin, with information on their use, threats and relations between the targeted habitats and the listed plants on the one hand and the knowledge associated with them and the socio-professional characteristics of the populations on the other. The data (user identity, plants used, plant organs collected, uses, plant threats) were collected from 113 individuals interviewed individually during an ethnobotanical study in 20 villages distributed around the three vegetation formations. The results showed that 59 plant species are useful for the populations surrounding the formations. The most important in terms of use value are Zanthoxylum zanthoxyloides (VUT = 7.86), Irvingia gabonensis (VUT = 7.84), Dialium guineense (VUT = 7.69), Khaya senegalensis (VUT = 7.46), Prosopis africana (VUT = 7.06), Ceiba pentandra (VUT = 7.01), and Synsepalum dulcificum (VUT = 6.98). The indices of Diversity and Equitability of the respondents reveal that knowledge on plant species is not homogeneously distributed (ID = 0.430, IE = 0.451 <0.5) and maximum information on species is held by a part of the population. Pruning (40%) is the main source of species threats. Plantation, agrosystems, sensitizing populations on good methods of harvest could help to preserve the main plants useful for the populations of Southern Benin.